Inhibition of Colorectal Cancer by Perillaldehyde Through Targeting SRD5A1 to Induce Autophagy via the PI3K/AKT Pathway - Leng Z; Zhang Y; Guo M; Chen Y; Wang Z (Drug Design, Development and Therapy)
Zhuyun Leng,1,* Yiqian Zhang,2,* Mingming Guo,3 Yan Chen,4 Zhiyong Wang2 1Endoscopy Center, Department of Gastroenterology, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, 200120, People’s Republic of China; 2Xiangan Hospital Xiamen University, China, School of Medicine, Xiamen University, Xiamen, 361100, People’s Republic of China; 3Naval Medical University, Shanghai, 200433, People’s Republic of China; 4Department of Pharmacy, Xiamen Susong Hospital, Xiamen, 361100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiyong Wang, Xiang’an Hospital of Xiamen University, School of Medicine, Xiamen University, Xiamen, 361100, People’s Republic of China, Email cywangzhiyong@126.com Yan Chen, Department of Pharmacy, Xiamen Susong Hospital, Xiamen, 361100, People’s Republic of China, Email wzychenyan@126.comBackground: Colorectal cancer (CRC) is the third most common cancer globally, with treatment challenges persisting. Perillaldehyde (PAH), a major active monomer extracted from Perilla, has shown potential against CRC, though its mechanisms remain unclear. This study aims to assess the therapeutic potential of PAH against CRC and to clarify its mechanisms of action, providing a rationale for PAH as a promising candidate for anti-CRC therapy.Methods: In vitro, we used CCK-8, colony formation, EdU assays, flow cytometry, and Western blotting to assess the effects of PAH on CRC cell proliferation and apoptosis. In vivo, a subcutaneous xenograft mouse model was established to evaluate the anti-CRC efficacy of PAH. Transcriptomic analysis was performed to identify possible mechanisms, particularly related to autophagy, and validated through TEM, immunofluorescence, Western blotting, and inhibitor assays. SRD5A1 was predicted as a potential target using Swiss Target Prediction and confirmed by molecular docking, molecular dynamics simulation, and CETSA. Bioinformatics analysis further assessed the clinical relevance and mechanism of SRD5A1, which was validated using a selective inhibitor.Results: PAH demonstrated inhibitory effects on CRC in both experimental models. RNA-seq and experimental validation suggest that PAH may inhibit CRC by modulating the PI3K/AKT pathway to induce autophagy. Bioinformatics analysis indicates that SRD5A1 could be a potential target of PAH, with PAH treatment reducing SRD5A1 levels and enhancing autophagic activity through PI3K/AKT suppression.Conclusion: PAH appears to inhibit CRC by targeting SRD5A1, thereby promoting autophagy through the PI3K/AKT pathway. This offers new perspectives for both the diagnosis and treatment of CRC. Keywords: perillaldehyde, colorectal cancer, autophagy, PI3K/AKT pathway, SRD5A1